Comparing the effects of chemical Ca2+ dyes and R-GECO on contractility and Ca2+ transients in adult and human iPSC cardiomyocytes - Robinson, P; Sparrow, AJ; Psaras, Y; Steeples, V; Simon, JN; Broyles, CN; Chang, Y-F; Brook, FA; Wang, Y-J; Blease, A; Zhang, X; Abassi, YA; et al. (Elsevier, 2023)
We compared commonly used BAPTA-derived chemical Ca2+ dyes (fura2, Fluo-4, and Rhod-2) with a newer genetically encoded indicator (R-GECO) in single cell models of the heart. We assessed their performance and effects on cardiomyocyte contractility, determining fluorescent signal-to-noise ratios and sarcomere shortening in primary ventricular myocytes from adult mouse and guinea pig, and in human iPSC-derived cardiomyocytes. Chemical Ca2+ dyes displayed dose-dependent contractile impairment in all cell types, and we observed a negative correlation between contraction and fluorescence signal-to-noise ratio, particularly for fura2 and Fluo-4. R-GECO had no effect on sarcomere shortening. BAPTA-based dyes, but not R-GECO, inhibited in vitro acto-myosin ATPase activity. The presence of fura2 accentuated or diminished changes in contractility and Ca2+ handling caused by small molecule modulators of contractility and intracellular ionic homeostasis (mavacamten, levosimendan, and flecainide), but this was not observed when using R-GECO in adult guinea pig left ventricular cardiomyocytes. Ca2+ handling studies are necessary for cardiotoxicity assessments of small molecules intended for clinical use. Caution should be exercised when interpreting small molecule studies assessing contractile effects and Ca2+ transients derived from BAPTA-like chemical Ca2+ dyes in cellular assays, a common platform for cardiac toxicology testing and mechanistic investigation of cardiac disease physiology and treatment.